2014
DOI: 10.1002/chem.201402354
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of RuII 4,4′‐Bi‐1,2,3‐triazolyl (btz) Complexes: Crystallographic Characterization of the Photoreactive Ligand‐Loss Intermediate trans‐[Ru(bpy)(κ2‐btz)(κ1‐btz)(NCMe)]2+

Abstract: We report the unprecedented observation and unequivocal crystallographic characterization of the meta-stable ligand loss intermediate solvento complex trans-[Ru(bpy)(κ2-btz)(κ1-btz)(NCMe)]2+ (1 a) that contains a monodentate chelate ligand. This and analogous complexes can be observed during the photolysis reactions of a family of complexes of the form [Ru()(btz)2]2+ (1 a–d: btz=1,1′-dibenzyl-4,4′-bi-1,2,3-triazolyl; =a) 2,2′-bipyridyl (bpy), b) 4,4′-dimethyl-2,2′-bipyridyl (dmbpy), c) 4,4′-dimethoxy-2,2′-bipy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 38 publications
6
51
0
Order By: Relevance
“…39,40 Recently, the single crystal structure of a monodentate intermediate species was obtained following photolysis of solutions of various bis-di-1,2,3-triazole complexes. 41 Figure 2a shows the structure of the starting bis-triazole and 2b illustrates the structure of the monodentate intermediate. What is most interesting is that the incoming acetonitrile ligand is trans to the coordinated singly bound bis-triazole.…”
Section: Factors Affecting Photosubstitutionmentioning
confidence: 99%
“…39,40 Recently, the single crystal structure of a monodentate intermediate species was obtained following photolysis of solutions of various bis-di-1,2,3-triazole complexes. 41 Figure 2a shows the structure of the starting bis-triazole and 2b illustrates the structure of the monodentate intermediate. What is most interesting is that the incoming acetonitrile ligand is trans to the coordinated singly bound bis-triazole.…”
Section: Factors Affecting Photosubstitutionmentioning
confidence: 99%
“…These energies can be determined or inferred spectroscopically, electrochemically and computationally and as [Ru(N^N) 3 ] 2+ complexes invariably have a highest occupied molecular orbital of predominantly metallic 4d character, and hence effectively the same ground state, these excited state energies can be readily compared). Work in our laboratory, [26][27][28] and those of others, [29][30][31][32] has shown that complexes containing 1,2,3-triazole rings that lack such steric promotion can also lead to photochemical reactivity, possibly through destabilisation of the 3 MLCT state with respect to the 3 MC state when compared to those states of the archetypal complex [Ru(bpy) 3 ] 2+ . We recently reported the series of complexes [Ru(bpy) 3-n (btz) n ] 2+ (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl, n = 1 to 3) 33 in which an increasing number of btz ligands leads to destabilisation of the 1 MLCT bands in the visible absorption spectrum, significantly so for the homoleptic complex [Ru(btz) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[8] Here,presence of the btz ligand appears to induce adestabilization of the 3 MLCT state,b ringing it into closer energetic proximity to the 3 MC state thereby enabling thermal population of the 3 MC state with consequential photochemical btz ligand ejection in acetonitrile solutions.Inthe case of the latter of these complexes,t his is accompanied by the unprecedented observation of am etastable ligand-loss intermediate, trans-[Ru(bpy)(k 2 -btz)(k 1 -btz)(NCCH 3 )] 2+ ,w hich can be formed quantitatively by photolysis in an NMR tube within minutes and has been crystallographically characterized. [9] Theb tz ligand has also been observed to induce photochemical decomposition in the iridium(III) complex [Ir(dfptz) 2 (btz)] + (dfptzH = 4-(2,4-difluorophenyl)-1,2,3-triazole) [10] which one would expect to be far more inert due to the typically higher lying 3 MC states associated with the 5d metal center.…”
mentioning
confidence: 99%